2021
DOI: 10.3389/fcell.2021.672009
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Mechanisms of Brain Endothelial Erythrophagocytosis

Abstract: The endothelial cells which form the inner cellular lining of the vasculature can act as non-professional phagocytes to ingest and remove emboli and aged/injured red blood cells (RBCs) from circulation. We previously demonstrated an erythrophagocytic phenotype of the brain endothelium for oxidatively stressed RBCs with subsequent migration of iron-rich RBCs and RBC degradation products across the brain endothelium in vivo and in vitro, in the absence of brain endothelium disruption. However, the mechanisms con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…All the studies demonstrating the phagocytic phenotype of the vascular endothelium were done using immortalized cells lines or in vivo rodent models. Our previous work, along with other studies, shows that the bEnd.3 cells [ 27 , 32 ] and HCMEC/D3 human brain microvascular endothelial cells [ 28 ] exhibit an erythrophagocytic phenotype for aged/damaged red blood cells. Since the red blood cell adhesion and phagocytic repertoire of the ihBMECs had not been reported, we determined the erythrophagocytic phenotype of the ihBMECs.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…All the studies demonstrating the phagocytic phenotype of the vascular endothelium were done using immortalized cells lines or in vivo rodent models. Our previous work, along with other studies, shows that the bEnd.3 cells [ 27 , 32 ] and HCMEC/D3 human brain microvascular endothelial cells [ 28 ] exhibit an erythrophagocytic phenotype for aged/damaged red blood cells. Since the red blood cell adhesion and phagocytic repertoire of the ihBMECs had not been reported, we determined the erythrophagocytic phenotype of the ihBMECs.…”
Section: Discussionmentioning
confidence: 93%
“…In accordance with the reported phagocytic phenotype of vascular endothelial cells, including the brain microvascular endothelial cells, our results show that ihBMECs also demonstrate cell adhesion and phagocytic characteristics ( Fig 4 ). This is the first study to show that the ihBMECs recapitulate the erythrophagocytic phenotype shown by the bEnd.3 cells [ 27 , 32 ] and human brain microvascular cells [ 28 ], making them a suitable in vitro model to study brain microvascular endothelial cell-red blood cell interactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations